Mexico's Human Rights Crisis - Anaya-Muñoz, Alejandro; Frey, Barbara (University of Pennsylvania Press, 2018)
Lawless elements are ascendant in Mexico, as evidenced by the operations of criminal cartels engaged in human and drug trafficking, often with the active support or acquiescence of government actors. The sharp increase in the number of victims of homicide, disappearances and torture over the past decade is unparalleled in the country's recent history. According to editors Alejandro Anaya-Muñoz and Barbara Frey, the "war on drugs" launched in 2006 by President Felipe Calderón and the corrupting influence criminal organizations have on public institutions have empowered both state and nonstate actors to operate with impunity. Impunity, they argue, is the root cause that has enabled a human-rights crisis to flourish, creating a climate of generalized violence that is carried out, condoned, or ignored by the state and precluding any hope for justice.Mexico's Human Rights Crisis offers a broad survey of the current human rights issues that plague Mexico.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 23. Jan 2019)
Keywords: Human Rights; Law; Political Science; Menschenrechtsverletzung; Gewalttätigkeit; Kriminalität; Mexiko; Aufsatzsammlung